23 Fractional factorial design for pvdf/pebax film composite synthesis on gas selectivity study - Sunarti, Abd Rahman; Mohamad Syafiq, Abdul Wahab; Nor Hanuni, Ramli; Abdul Latif, Ahmad (Universiti Malaysia Pahang, 2018)
One of the key indicators for membrane film excellencies is by having a good ideal selectivity, and it is defined as the permeability ratio of two pure gases which be separated. This study was focusing on factors screening and interaction study between involved factors in film development on gas selectivity by employing 23 fractional factorial design (FFD). A total of four factors; Pebax concentration, bath temperature, evaporation times and quenching times which obtain from past research was chose to run simultaneously and ideal selectivity was chose as a single respond. Order of contribution was found to be as follows; Pebax concentration > quenching times > bath temperature > evaporation times, while the most impacting factors towards gas selectivity was Pebax concentration (main effect), evaporation times - Pebax concentration (interaction effect), quenching times (main effect). The outcome of the study indicates a very strong judgement in utilizing FFD to minimize and eliminate factors by considering the interaction among the factors involves in membrane film development for a perfect gas selectivity.